Terrorism in Africa : the evolving front in the War on Terror / edited by John Davis. - Davis, John, 1962- (Lexington Books, 2010)
The study, Terrorism in Africa: The Evolving Front in the War on Terrorism, represents a research endeavor aimed at increasing scholarly discourse on the ever-expanding threat of terrorism and terrorist related violence in the region. It offers the most wide-ranging analysis of the sub-national and transnational terrorists groups that have made Africa the second most violent region in the world.